Reinforcing the Immunocompromised Host Defense against Fungi: Progress beyond the Current State of the Art - Georgios Karavalakis; Evangelia Yannaki; Anastasia Papadopoulou (Journal of Fungi, 2021)
Despite the availability of a variety of antifungal drugs, opportunistic fungal infections still remain life-threatening for immunocompromised patients, such as those undergoing allogeneic hematopoietic cell transplantation or solid organ transplantation. Suboptimal efficacy, toxicity, development of resistant variants and recurrent episodes are limitations associated with current antifungal drug therapy. Adjunctive immunotherapies reinforcing the host defense against fungi and aiding in clearance of opportunistic pathogens are continuously gaining ground in this battle. Here, we review alternative approaches for the management of fungal infections going beyond the state of the art and placing an emphasis on fungus-specific T cell immunotherapy. Harnessing the power of T cells in the form of adoptive immunotherapy represents the strenuous protagonist of the current immunotherapeutic approaches towards combating invasive fungal infections. The progress that has been made over the last years in this field and remaining challenges as well, will be discussed.